Water, Sanitation, and Maternal Behavioral Factors Associated with Diarrhea Risk in Children 10–59 Months: An Epidemiological Analysis - Showell, Jack Okon; Mwasaru, Boniface Mwadime (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines the relationship between clean water sanitation facilities and maternal health behaviors in relation to the incidence of diarrhea among toddlers aged 10–59 months, a persistent public health problem in many developing regions. Despite ongoing improvements in water and sanitation infrastructure, diarrhea remains a leading cause of morbidity in early childhood, suggesting that behavioral factors may play a crucial mediating role. Methodology: This research employed a quantitative cross-sectional design involving 90 toddlers, with data collected through structured interviews with mothers and direct household observations to capture both environmental sanitation conditions and daily hygiene practices. Main Findings: The results of the study showed that 35.6% experienced diarrhea and 64.4% did not experience diarrhea. Then, from the bivariate results with α 5%, two variables were found to be related to the incidence of diarrhea in toddlers, namely the use of latrines with a p-value of 0.024 and handwashing habits with a p-value of 0.050. Meanwhile, the variables of clean water sanitation facilities (pv 0.082) and boiling water (pv 1.000) did not have a significant relationship with diarrhea. Novelty/Originality of this study: The novelty of this study lies in its integrated analysis of environmental sanitation and maternal practices, demonstrating that behavior-related factors may exert a stronger influence on diarrhea prevention than infrastructure alone. By highlighting the interaction between sanitation access and maternal behavior, this study provides new empirical evidence to support community-based health interventions that prioritize behavioral change communication alongside sanitation development.